115k views
1 vote
Using the function below:
{(-5,2),(1,1),(5,1),(2,6)}
f(1) =
f(2)=

User Iloveitaly
by
4.8k points

1 Answer

3 votes


\bf \{(-5,2),(1,1),(5,1),(2,6)\}\implies \begin{array}ll \cline{1-2} x&f(x)\\ \cline{1-2} -5&2\\ 1&1\\ 5&1\\ 2&6\\ \cline{1-2} \end{array} \begin{array}{llll} \\[1em] \leftarrow f(1) = 1\\\\ \leftarrow f(2)=6 \end{array}

User Nur Iman Izam
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.